Blood pressure levels post mechanical thrombectomy and outcomes in non-recanalized large vessel occlusion patients. (11th January 2018) - Goyal, Nitin; Tsivgoulis, Georgios; Pandhi, Abhi; Dillard, Kira; Alsbrook, Diana; Chang, Jason J; Krishnaiah, Balaji; Nickele, Christopher; Hoit, Daniel; Alsherbini, Khalid; Alexandrov, Andrei V; Arthur, Adam S; et al.
Abstract : Objective: Permissive hypertension may benefit patients with non-recanalized large vessel occlusion (nrLVO) post mechanical thrombectomy (MT) by maintaining brain perfusion. Data evaluating the impact of post-MT blood pressure (BP) levels on outcomes in nrLVO patients are scarce. We investigated the association of the post-MT BP course with safety and efficacy outcomes in nrLVO. Methods: Hourly systolic BP (SBP) and diastolic BP (DBP) values were prospectively recorded for 24 hours following MT in consecutive nrLVO patients. Maximum, minimum, and mean BP levels were documented. Three-month functional independence (FI) was defined as modified Rankin Scale (mRS) scores of 0–2. Results: A total of 88 nrLVO patients were evaluated post MT. Patients with FI had lower maximum SBP (160±19 mmHg vs 179±23 mmHg; P=0.001) and higher minimum SBP levels (119±12 mmHg vs 108±25 mmHg; P=0.008). Maximum SBP (183±20 mmHg vs 169±23 mmHg; P=0.008) and DBP levels (105±20 mmHg vs 89±18 mmHg; P=0.001) were higher in patients who died at 3 months while minimum SBP values were lower (102±28 mmHg vs 115±16 mmHg; P=0.007). On multivariable analyses, both maximum SBP (OR per 10 mmHg increase: 0.55, 95% CI 0.39 to 0.79; P=0.001) and minimum SBP (OR per 10 mmHg increase: 1.64, 95% CI 1.04 to 2.60; P=0.033) levels were independently associated with the odds of FI. Maximum DBP (OR per 10 mmHg increase: 1.61; 95% CI 1.10 to 2.36; P=0.014) and minimum SBP (OR per 10 mmHg increase: 0.65, 95% CI 0.47 to 0.90; P=0.009) values were independent predictors of 3-month mortality. Conclusions: Our study demonstrates that wide BP excursions from the mean during the first 24 hours post MT are associated with worse outcomes in patients with nrLVO.